An integrated model for motor control of song in Serinus canaria. Issue 3 (October 2016) - Alonso, Rodrigo Gogui; Amador, Ana; Mindlin, Gabriel B.
Highlights: We proposed a computational model for birdsong production. The neural model generates realistic pressure and syringeal tension gestures. The gestures obtained drive a biomechanical model to synthesize realistic songs. We assume for HVC activity a continuous component and input from the brainstem. Abstract: Birdsong is a learned motor behavior controlled by an interconnected structure of neural nuclei. This pathway is bilaterally organized, with anatomically indistinguishable structures in each brain hemisphere. In this work, we present a computational model whose variables are the average activities of different neural nuclei of the song system of oscine birds. Two of the variables are linked to the air sac pressure and the tension of the labia during canary song production. We show that these time dependent gestures are capable of driving a model of the vocal organ to synthesize realistic canary like songs.